The features of Hellenistic poetics in Aratus’ Phaenomena - Garbačiauskas, Paulius (Literatūra, 2007)
Soon after its appearance, the Phaenomena – didactic poem composed around 276 by Aratus of Soli– became widely read and commented in the Hellenistic world and late Antiquity. It consists of 1152 hexameter lines and is preserved exclusively intact. While the character and language of the poem are rather clearly Hesiodic, its content, as far as the astronomic material is concerned, is basically derived from Eudoxus of Cnidus and reflects the cosmic beliefs of the contemporary Old Stoa, exposing Zeus as the benevolent life-giving force, which has established the cosmos as such, and which is eager to reveal his perpetual signs to men. Eudoxus, being Aratus’ primary source, is displayed by another professional astronomer Hipparchus of Nicaea, who has written a comprehensive commentary on both Aratus and Eudoxus. However, despite its immense popularity in the Hellenistic world, the Phaenomena – or ‘un poème aussi oublié que les Phénomènes d’Aratos’, as J. Martin (1956, 5) prefers to put it – had to hold on for another millennium to be properly explored. While composing his poem from the prose text of μαθηματικός Eudoxus, which ought to be treated as particularly technical, Aratus invoked a sophisticated system of imitation and variation. His text, where mathematical and geometrical material is versified incredibly fluently, is imbued with complex chiastic structures, elegant periodic sentences, delimitative homoeoteleuta and anaphors, internal rhymes, alliterations, slight touches of humour, verbal puns, and even acrostics (e.g. the word ΛΕΠΤΗ encrypted in 783–7, which denotes the whole aesthetical programme of the Hellenistic literature). All these ornaments, as well as the general elegance of the text, are essentially responsible for one of the most important principles of the Hellenistic poetics – λεπτότης, standing for ‘subtlety’, ‘refinement’ of the style, which is closely related to Callimachus, perhaps the most influential opinion-maker and icon of the Hellenistic literature, who calls in his epigram Aratus’ verses λεπτα żσιες (AP 9.507.3–4) thus highlighting the aforementioned acrostic and demonstrating its recognition. Even more subtle Hellenistic features lie behind the structure of the poem as a whole. It seems that the time and space of the narrative are somewhat limitless and eternal, which enables us reading the Phaenomena both as successor and predecessor of the Hesiodic poems, while the space limited only by the ocean, which stands for the horizon, at the same time infinitely expands the spatial pattern of the narrative. Thus, the eternity of the time corresponds and correlates to the endlessness of the space, which, again, elaborately embodies this principle of the ‘refinement’, at the very same time perceived in different layers of the semantically rich narrative. Furthermore, the poem can itself be regarded as the celestial sphere, a kind of micro-cosmos projected to the macro-cosmos, which is shaped by Stoic Zeus. Aratus delivers his balanced text – the Phaenomena – to the reader exactly the same way as Zeus reveals to men his eternal signs – the phaenomena. At the same time his poem becomes one of the divine phenomena and is to be regarded as hierarchically superior to all other signs, through which they are exclusively interpreted and revealed. Thus being part of all possible phenomena, the poem is unclosed as the whole comprising all other signs that would not be valuable as such or even exist without the presence of the former. The embodiment of principles of the Hellenistic poetics – λεπτότης to be mentioned the first – may be clearly seen from quite different perspectives and levels of this extremely rich narrative, intelligibility of which entirely depends on the reader’s scholarship.